High-temperature-resistant superfine zirconium-based yellow ceramic pigment and preparation method thereof

The liquid-phase method for preparing ultrafine zirconium-based yellow ceramic pigments solves the problems of environmental unfriendliness and reduced tinting strength in traditional methods. It achieves stable Tb4+ in an air atmosphere and produces zirconium-based yellow ceramic pigments with high temperature resistance, ultrafine particle size, and strong tinting strength, demonstrating high process feasibility and stability.

CN121470503APending Publication Date: 2026-02-06HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511580258.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Traditional zirconium-based yellow ceramic pigments have problems such as being environmentally unfriendly during preparation, reduced coloring power after ultrafine pigment processing, and difficulty in stabilizing Tb4+ under normal conditions, resulting in uneven coloring and insufficient high-temperature resistance.

Method used

Ultrafine zirconium-based yellow ceramic pigments were prepared using a liquid-phase method. By controlling the concentrations of zirconium, terbium, and cerium ions and the ratio of citric acid, a uniform complex was formed. Combined with ammonium fluoride precipitation and calcination in an air atmosphere, the stability of Tb4+ and the high-temperature stability of zirconium silicate were ensured, achieving ultrafine particle size and high coloring power.

Benefits of technology

The method achieves stable Tb4+ in air atmosphere, and prepares zirconium-based yellow ceramic pigments with ultrafine particle size, strong coloring power, high temperature resistance and environmental protection. It solves the environmental hazards and performance contradictions in traditional methods, and has high process feasibility and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121470503A_ABST
    Figure CN121470503A_ABST
Patent Text Reader

Abstract

According to the high-temperature-resistant superfine zirconium-based yellow ceramic pigment and the preparation method thereof, Ce < 4 + > doping enhanced color generation is provided aiming at insufficient color generation of a superfine terbium yellow pigment, and the problem of yellow green color tone easily occurring in traditional terbium doping is solved; a liquid phase method is adopted for mixing from a molecular level, so that coarse and uneven particles caused by grinding by a solid phase method are avoided; through the charge compensation effect of Ce < 4 + >, the stability of Tb < 4 + > can be realized in a conventional air atmosphere, and the Tb < 4 + > can be stabilized only through one-time calcination in the air atmosphere, and the calcination temperature is far lower than that of a traditional solid phase method. The prepared pigment has the comprehensive advantages of ultrafine particle size, high tinting strength, high stability, high process feasibility and the like, and also has the characteristics of pure and saturated color generation, excellent dispersity, environmental protection, energy conservation, good process stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of inorganic non-metal, and relates to a ceramic colorant and a preparation method thereof. BACKGROUND

[0002] The ceramic colorant is a key material for imparting color to ceramic products, and its performance directly affects the appearance and value of the products. Among many colorants, zirconium-based colorants with zirconium silicate as the matrix become important coloring materials for high-end ceramics due to their excellent chemical stability and high-temperature resistance. With the increasing aesthetic requirements of the market for high-end ceramics such as super-flat glaze and rock plate, higher standards are put forward for the color purity, saturation and glaze texture of the colorant. Traditional micron-level colorants are prone to cause uneven glaze color, while rare earth terbium (Tb) ions become an ideal choice for realizing high-purity yellow due to their ability to produce bright yellow emission in the form of Tb 4+ ). However, the application of this technology faces two major challenges: first, Tb 4+ is extremely unstable under normal conditions and is easily reduced to the trivalent state, and existing stabilization processes rely on strong corrosive atmospheres such as chlorine gas, which is contrary to the green production concept; second, the traditional method of promoting grain growth by increasing the calcination temperature will cause particle coarsening, and it is difficult to balance ultra-fining and high color performance. SUMMARY

[0003] To solve the problem of non-environmental preparation process of yellow ceramic colorant and the decrease in coloring power after ultra-fining of the colorant as described in the background, the present application provides a high-temperature-resistant ultra-fine zirconium-based yellow ceramic colorant and a preparation method thereof, which overcomes the color fading problem brought by the ultra-fining of the yellow ceramic colorant, and ultimately prepares a new type of yellow ceramic colorant with ultra-fine particle size, high coloring power, high stability and high process feasibility.

[0004] The first aspect of the present application provides a preparation method of a high-temperature-resistant ultra-fine zirconium-based yellow ceramic colorant, comprising: dissolving a zirconium source, a terbium source and a cerium source in deionized water in sequence to obtain a metal ion solution, wherein the concentration of zirconium ions in the metal ion solution is 0.1-3 mol / L, and the total concentration of terbium ions and cerium ions is 0.01-0.3 mol / L; adding citric acid to the metal ion solution, stirring uniformly to fully dissolve and complex, and obtaining a complex solution; adding a mixed solution of tetraethyl orthosilicate and ethanol to the complex solution, stirring uniformly, and obtaining a precursor mixed solution, wherein the concentration of silicon in the precursor mixed solution is 0.01-5 mol / L; slowly adding an aqueous ammonium fluoride precipitant to the precursor mixed solution under vigorous stirring, continuing to stir and age for a period of time after the addition is completed, and forming a uniform white gel-like precipitate; The white gelatinous precipitate is washed with water for multiple times and then washed with alcohol for multiple times, and then dried to obtain a precursor powder; The mineralizer is added into the precursor powder, mixed well, and calcined in an air atmosphere. After the calcination is completed, the calcination product is cooled to room temperature in the furnace to obtain a calcination product; The calcination product is ground to obtain an ultra-fine zirconium-based yellow ceramic colorant.

[0005] Further, the zirconium source comprises zirconium oxychloride; the terbium source comprises terbium chloride; and the cerium source comprises cerium chloride.

[0006] Further, in the metal ion solution, the concentration of zirconium ions is 0.5-2 mol / L.

[0007] The concentration of zirconium ions needs to be limited in consideration of the solution flowability and subsequent processing efficiency: if the concentration is too low, the solution is too dilute, the yield of the obtained product is low, and it is not conducive to large-scale industrial production; if the concentration is too high, the viscosity of the solution increases, and uneven mixing may occur when stirring and adding the precipitant, and the washing and filtering processes are difficult, thereby reducing the production efficiency. If the concentration of the zirconium source, which is the main raw material for preparing the zirconium-based colorant, is too high, the raw material will be wasted (if the subsequent process cannot completely react), and the cost will be increased; if the concentration is too low, the output efficiency of the unit volume of the solution will be reduced, and the production energy consumption and time cost will be indirectly increased; the range of 0.5-2 mol / L can maximize the production efficiency of the unit batch while ensuring the utilization rate of the raw material, and balance the cost and production capacity.

[0008] Further, in the metal ion solution, the total concentration of terbium ions and cerium ions is 0.01-0.2 mol / L.

[0009] The total concentration of terbium ions and cerium ions is limited to ensure the realization of both coloring and stability effects. Terbium ions (Tb 4+ ) are the core of yellow presentation, and the concentration directly determines the coloring intensity and saturation of the colorant. The lower limit of the total concentration is set to 0.01 mol / L to ensure that there are enough Tb 4+ ions in the system to avoid weak yellow emission signal and light yellow colorant, which cannot meet the demand of high-end ceramics for high-purity yellow; the core function of cerium ions (Ce 4+ ) is to inhibit Tb 4 + being reduced to Tb 3+ . The total concentration needs to provide sufficient Ce ions to form a synergistic effect with Tb 4+ through the redox characteristics to ensure the stability of Tb 4+ in the air atmosphere calcination; if the total concentration is less than 0.01 mol / L, the number of Ce ions is insufficient to effectively block Tb 4+The reduction of Tb3+ and Ce3+ ions will lead to the degradation of color performance. At the same time, it is necessary to prevent the total concentration of Tb3+ and Ce3+ ions from being too high to destroy the structure and performance of the colorant. If the total concentration is higher than 0.2 mol / L, the density of Tb3+ and Ce3+ ions in the system is too large, which exceeds the “capacity limit” of the zirconium silicate matrix. The excess doped ions are prone to agglomerate in the matrix to form a local high-concentration area, which not only leads to uneven color of the glaze, but also destroys the integrity of the crystal structure of the zirconium silicate matrix (formation of impurity phase), reduces the high-temperature resistance and chemical stability of the colorant; high concentration of Tb3+ ions will lead to the decrease of the crystallinity of the zirconium silicate matrix, and the increase of the impurity phase. When mixed with glaze, it reduces the stability and corrosion resistance of the colorant; controlling the total concentration within 0.2 mol / L can effectively avoid this problem and ensure that every Tb 4+ can efficiently participate in coloration and maintain high color strength of the colorant.

[0010] The concentration of zirconium ions in the metal ion solution is 0.5-2 mol / L, which is the main body of the zirconium silicate matrix; the total concentration of Tb and Ce ions as doped components (0.01-0.2 mol / L) needs to form a reasonable “host-doping” ratio with the concentration of zirconium ions, which will not cause functional failure due to too little doping amount, nor will it occupy the lattice position of zirconium ions due to too much doping amount, so as to ensure the normal formation of the zirconium silicate matrix and the uniform dispersion of the doped ions. In addition, during the preparation of the precursor, Tb and Ce ions need to form a uniform complex with zirconium ions and citric acid. Too high total concentration will lead to local ion concentration imbalance, and it is difficult for citric acid to fully complex with the three ions, which is prone to uneven complexation; controlling the total concentration of Tb and Ce ions within 0.01-0.2 mol / L can ensure that the three ions are complexed with citric acid in proportion, which lays the foundation for the subsequent formation of uniform gel precipitation and the preparation of ultra-fine colorant.

[0011] Further, the ratio of the number of moles of citric acid to the total number of moles of metal ions of zirconium ions, terbium ions and cerium ions is (1.5-3.0):1.

[0012] This molar ratio is limited to ensure that citric acid can fully exert its complexing effect and avoid negative effects caused by its excess. The key is to balance the “complexing efficiency, precursor quality and process cost” of the three parameters; first, ensure the complete complexation of metal ions and avoid local enrichment: citric acid is a ternary carboxylic acid, each molecule can complex with metal ions (Zr 4+ , Tb 4+ , Ce 4+) to form stable chelate. The lower limit ratio of 1.5:1 is calculated based on the total coordination number of metal ions, which can provide sufficient complexing sites for all metal ions in the system to ensure no free metal ions are left; if the ratio of citric acid is lower than 1.5:1, part of the metal ions cannot be complexed with citric acid and will be free in the solution. These free ions are prone to react prematurely to form precipitates when mixed with the silicon source or when the precipitant is added dropwise, resulting in uneven precursors and ultimately affecting the particle size and color consistency of the pigments; second, control the stability of the complex to adapt to the subsequent process: the complexing stability of citric acid and metal ions needs to be "moderate", which should be stable enough to prevent the premature reaction of metal ions, and should be able to decompose smoothly during the subsequent calcination process without leaving carbon impurities; a ratio of (1.5-3.0):1 can form a complex with moderate stability, which can support the uniform dispersion of the precursor preparation stage and completely decompose during calcination to avoid carbon residues causing the pigments to turn black or have impure color; if the ratio of citric acid is higher than 3.0:1, it will form a complex that is too stable; such complexes may hinder the combination of silicon-oxygen tetrahedron and metal ions when mixed with the silicon source subsequently, affecting the formation of zirconium silicate matrix; at the same time, excessive citric acid will increase the energy consumption during the drying stage, and a large amount of gas may be produced during calcination, which may cause the precursor powder to crack; third, balance the cost and process efficiency to avoid waste of resources: as a complexing agent, excessive use of citric acid will directly increase the cost of raw materials; the upper limit ratio of 3.0:1 is to minimize the use of citric acid while ensuring complete complexation, avoiding unnecessary cost waste; if the ratio of citric acid is too high, it will increase the viscosity of the complexing solution, affecting the uniformity of subsequent operations such as stirring and adding precipitant; a ratio of (1.5-3.0):1 can maintain good fluidity of the solution, ensuring stable control of each step of the process and improving production efficiency.

[0013] Further, the concentration of silicon in the precursor mixture is 0.01-1 mol / L.

[0014] The chemical formula of zirconium silicate is ZrSiO4, and the zirconium silicate matrix is a carrier of Tb 4+ (chromatic) and Ce ions (stabilizing), and its structural integrity directly affects the dispersion of doped ions and the stability of pigments. The molar ratio of Si and Zr is usually set to 1.2 because part of the silicon source is lost during preparation. If the silicon concentration is lower than 0.01 mol / L, insufficient silicon source will result in insufficient formation of the zirconium silicate matrix, which cannot effectively protect the doped ions, and is prone to ion aggregation or diffusion loss at high temperatures, reducing the color intensity and high temperature resistance; if the silicon concentration is too high, excessive Si 4+The amorphous SiO2 phase will be formed in the matrix, which will destroy the lattice structure of zirconium silicate, resulting in the decrease of mechanical strength and chemical stability of the colorant. At the same time, in the precursor mixed solution, the silicon source (tetraethyl orthosilicate and ethanol mixed solution) needs to be uniformly mixed with the metal ion-citric acid complex; if the silicon concentration is too high, the hydrolysis rate of tetraethyl orthosilicate will accelerate, and it is easy to form high-concentration silicon-oxygen polymer in the local area, which cannot be fully combined with the metal ion complex, resulting in uneven distribution of silicon in the precursor, eventually causing composition segregation of the colorant, some areas without coloring, some areas with dull color, also affecting the stirring uniformity and the diffusion efficiency of the subsequent precipitant (ammonium fluoride), and easily forming local precipitation agglomeration; if the silicon concentration is lower than 0.01 mol / L, the silicon source is too sparse, and the mixing efficiency with the metal ion complex is low, which will also lead to uneven formation of zirconium silicate matrix, affecting the performance consistency of the colorant. The melting point of the zirconium silicate matrix is high (about 2500°C), which is the core guarantee of the high temperature resistance of the colorant. The zirconium silicate crystal structure formed within the silicon concentration range of 0.01-1 mol / L is complete, which can remain stable during high-temperature sintering of ceramics (usually 1000-1300°C), avoiding decomposition or discoloration of the colorant; if the silicon concentration deviates from this range, the matrix defects increase, which is easy to cause crystal type transformation or reaction with glaze at high temperature, resulting in color fading; the excess of silicon source (tetraethyl orthosilicate), i.e. exceeding the range of Si / Zr=1.2, will increase the raw material cost, and the excess silicon may form a glass phase during calcination, reducing the purity of the colorant; too low silicon concentration will reduce the colorant output efficiency per unit volume of solution, increasing the energy consumption in the drying, calcination and other links. The concentration of 0.01-1 mol / L can maintain a moderate viscosity of the mixed solution, ensuring that the stirring, adding precipitant and other steps can be carried out stably, providing a process basis for forming a uniform gel-like precipitate, while ensuring the quality of the matrix, achieving a balance between raw material utilization and production efficiency.

[0015] Further, the concentration of the precipitant ammonium fluoride aqueous solution is 1.0-4.0 mol / L, the precipitant ammonium fluoride aqueous solution is slowly added to the precursor mixed solution under vigorous stirring, after the addition is completed, the stirring is continued for 2-8 hours for aging, and a uniform white gel-like precipitate is formed.

[0016] In the concentration limitation of the precipitant ammonium fluoride aqueous solution, 1.0 mol / L is the lower limit of the concentration, which can provide sufficient F - for rapid reaction with metal ions (Zr 4+ , Tb 4+ , Ce 4+ ) to generate fluoride precipitate, avoiding incomplete precipitation due to insufficient F - , or too slow reaction rate to prolong the production cycle. 4.0 mol / L is the upper limit of the concentration, which can prevent local reaction "boiling" caused by too high F - concentration, if the concentration exceeds 4.0 mol / L, the local F- Concentration shock will quickly generate a large number of fine precipitates and agglomerate, unable to form a uniform gel-like structure, ultimately affecting the super-fine particle size and dispersion of the colorant. At the same time, F - If excessive, it will be adsorbed on the surface of the precipitate, and it is difficult to completely remove in subsequent washing; residual F - May react with zirconium silicate matrix during calcination, destroying the crystal lattice structure and reducing the stability of the colorant. The core role of aging is to further adjust the structure of the preliminarily formed fluoride-silicon source mixed precipitate. During the aging process, the unreacted metal ions and silicon source in the system can continue to slowly diffuse and fill the small gaps inside the precipitate, reducing structural defects. This ensures that the zirconium silicate matrix forms more completely during subsequent calcination, and the doped ions (Tb 4+ , Ce 4+ ) are more evenly dispersed, avoiding uneven coloration or reduced stability of the colorant due to precursor defects. Two hours is the lower limit for aging, which allows fine precipitate particles to "grow" through a slow dissolution-precipitation process and arrange more closely, enhancing the mechanical strength of the gel and preventing it from breaking during subsequent washing; eight hours is the upper limit for aging, which prevents the precipitate particles from growing too much, clumping, or the gel from shrinking and cracking due to water loss, ensuring that the precursor remains in a uniform gel state and facilitating subsequent drying. A concentration of 1.0-4.0 mol / L can ensure complete precipitation while reducing the amount of F - excessively remaining, reducing washing difficulty and process risk.

[0017] Further, the white gel-like precipitate is washed with water for 2-6 times and then washed with ethanol for 2-6 times, and then dried at 80-120 ℃ for 12-24 h to obtain a precursor powder.

[0018] The combined operation of water washing and ethanol washing has the core role of removing impurities from the precursor precipitate in stages, optimizing the efficiency of subsequent drying, and laying the foundation for the purity and performance of the final colorant. Water washing efficiently removes water-soluble impurities. First, it removes excess precipitants and reaction byproducts: during the precipitation reaction, ammonium fluoride (NH4F) may be in excess, and the reaction generates NH4 + , etc. Water washing can remove these free NH4 + , F - , and unreacted ammonium fluoride through dissolution, avoiding impurity residues. If these ions are not removed, NH3 and HF gases will be generated during subsequent calcination, not only corroding the equipment but also damaging the zirconium silicate matrix structure, leading to pores or abnormal coloration of the colorant. Second, it washes away uncomplexed metal ions and residual citric acid: there may be free metal ions (Zr 4+ , Tb 4+ , Ce4+ ), and excess citric acid. Water washing can dissolve and remove these substances, preventing them from forming impurity phases after drying, affecting the purity and uniformity of the pigment — for example, residual citric acid can carbonize during calcination, causing the pigment to darken; free metal ions can form non-target oxides, reducing the high-temperature resistance of the pigment. The role of ethanol washing is to optimize drying efficiency and precursor structure. First, reduce the water content of the precipitate to speed up subsequent drying: ethanol is miscible with water and has a boiling point (78°C) much lower than water (100°C), and the surface tension of ethanol is smaller, which can quickly replace the water inside and on the surface of the precipitate. After ethanol washing, the water content in the precipitate is greatly reduced, and during subsequent drying at 80-120°C, the drying time can be shortened, energy consumption can be reduced, and hard agglomeration of precursor particles caused by long-time high-temperature drying can be avoided. Second, inhibit metal ion hydrolysis and protect the stability of the precursor: some metal ions (such as Zr 4+ ) are prone to hydrolysis in a humid environment, generating hydroxide impurities such as Zr (OH)4; the presence of ethanol can reduce the polarity of the system, inhibit the hydrolysis tendency of metal ions, and ensure that the precursor maintains a stable fluoride-silicon source composite structure before drying, avoiding interference with the formation of zircon silicate matrix by hydrolysis products during subsequent calcination. In addition, a single washing cannot completely remove all impurities, and 2-6 washes are the optimal interval verified by experiments. Less than 2 times, water-soluble impurities and water residues are too much, affecting the performance of the pigment; more than 6 times, although the purity can be further improved, it will increase the consumption of ethanol and water resources, prolong the production cycle, and increase the cost; multiple gentle washing can avoid the destruction of the gel-like precipitate structure caused by single strong washing, ensuring that the precursor maintains a uniform porous structure. This structure is beneficial to gas escape and uniform grain growth during subsequent drying and calcination, ultimately forming pigment particles with ultra-fine and good dispersity.

[0019] Further, 5-20 wt% of a mineralizer is added to the precursor powder, mixed thoroughly, and calcined in an air atmosphere. The calcination conditions are as follows: heating at a rate of 2-5 °C / min to 800-1100 °C, and maintaining at this temperature for 20 min-4 h; after calcination, the furnace is cooled to room temperature to obtain. The mineralizer is LiF.

[0020] The mineralizer reacts with the components in the precursor to form a low-melting-point liquid phase, reducing the generation temperature of zirconium silicate (ZrSiO4); 5 wt% is the lower limit of the function. If the addition amount is less than 5 wt%, the amount of liquid phase is insufficient, the grain growth is slow and defects are prone to occur, affecting the color stability of the pigment. By ensuring the formation of sufficient liquid phase in the system, the growth of Zr 4+ and Si 4+diffusion and reaction, so that the zircon silicate lattice can be completely formed at 800-1100℃ (lower than the traditional process of 1200℃ or more), avoiding the increase of calcination temperature and energy consumption due to insufficient mineralizer, or insufficient crystallization of zircon silicate; if higher than 20 wt%, the excess liquid phase will accelerate the grain agglomeration and coarsening, destroying the superfine characteristics of the colorant, and failing to meet the requirements of high-end ceramics on particle size; at the same time, the excessive addition of mineralizer will cause part of the mineralizer to be unable to completely volatilize, remaining in the colorant; these residual mineralizers will destroy the integrity of the zircon silicate lattice, reduce the high temperature resistance and chemical stability of the colorant, and even react with glaze during ceramic sintering, causing defects such as pinholes and devitrification on the glaze surface, affecting the appearance of the product; the excess mineralizer may also interact with the doping ions (Tb 4+ 、Ce 3+ / Ce 4+ ), for example, Li + in the mineralizer LiF may occupy the lattice position of the doping ion, or change the redox environment of the system, causing Tb 4+ to be reduced to Tb 3+ , weakening the yellow color intensity; at the same time, it may also affect the stabilizing effect of Ce ions on Tb 4+ , ultimately leading to a decline in the performance of the colorant. In addition, the present application adopts air atmosphere calcination, and the addition amount of 5-20 wt% of the mineralizer can be synergized with the heating rate of 2-5 ℃ / min and the holding temperature of 800-1100℃: it can fully play the mineralization effect under the process conditions, and gradually volatilize during the holding stage to reduce the residue; if the addition amount of the mineralizer is too high, it is difficult to completely remove the residue even if the holding time is prolonged, increasing the process control difficulty. At the same time, the mineralizer has a certain cost, and the lower limit of 5 wt% can ensure the basic mineralization effect, and the upper limit of 20 wt% can avoid waste of raw materials, ensuring that the performance of the colorant meets the standards, controlling the production cost, and improving the economic efficiency and industrialization feasibility of the process.

[0021] Based on the above preparation method, the second aspect of the present application proposes a high-temperature-resistant superfine zircon-based yellow ceramic colorant, whose structural general formula is Tb x Ce y Zr 1-x-y SiO4; wherein 0

[0022] The core of the superfine zircon-based yellow ceramic colorant of the present application is a zircon silicate (ZrSiO4) matrix, which has a zircon-type crystal structure, Zr 4+ occupies the cation site in the lattice, and forms a stable structure with SiO4 4- tetrahedron, and the general formula “Zr1₋ xThe "Tb1-x-yZryCe xSiO4" part accurately reflects this host. At the same time, Tb and Ce ions are used to replace part of the lattice sites of Zr 4+ , which conforms to the typical structural design of "doped zirconium-based colorants". The expression "Tb x Ce y " in the general formula accurately reflects the doping mode of the two ions replacing Zr 4+ , and the sum of "x+y" corresponds to the substitution ratio, which conforms to the core design of the present application "composite doping". Overall, Tb x Ce y Zr 1-x-y SiO4's structural formula matches the technical solution of the present application "using zirconium silicate as the matrix, and Tb, Ce as the doping ions".

[0023] In addition, Tb 4+ is responsible for yellow coloration, and the oxidizing property of Ce 4+ is responsible for stabilizing Tb 4+ . The structural formula can be further improved and expressed as: Tb 4+ x Ce 4+ ᵧ Zr1₋ x ₋ᵧ SiO4, to clearly associate valence and function. According to the preparation process of the present application, the total concentration of Tb and Ce ions (corresponding to x+y) needs to match the concentration of Zr ions. In the metal ion solution, the total concentration of terbium ions and cerium ions is 0.01-0.3 mol / L, and the concentration of zirconium ions is 0.1-3 mol / L, i.e. the value of x+y is much less than 1, usually 0.01-0.1, which belongs to low concentration doping. The range of x and y in the general formula can be further limited to "0 < x + y << 1" to reflect the characteristics of "small amount of doping, without destroying the matrix structure", which is more consistent with the actual amount of doping in preparation.

[0024] Compared with the prior art, the present application has the following beneficial effects: (1) pure color and strong coloring power: to solve the problem of insufficient coloration of superfine terbium yellow pigment, Ce 4+ doping is introduced to enhance coloration; this is because Ce 4+ ions have oxidizing properties under high temperature conditions, which can prevent the system from being unstable Tb 4+ from being converted to Tb 3+ , because Tb 3+ is not conducive to color development and is harmful to color development, or in other words, Ce 4+ can oxidize more Tb 3+ in the system to Tb 4+ , enhancing coloration; in addition, Ce 4+ions form new lower Ce 4f impurity energy levels in the zirconium silicate lattice, absorb red shift, enhance color rendering; Overall, the present application, through the synergistic effect of Ce 4+ and Tb 4+ , on the one hand, Ce 4+ can optimize the electronic transition efficiency of the pigment, enhance the yellow emission intensity of Tb 4+ ; on the other hand, the composite doped system formed by the two can reduce the grain defects, improve the color rendering purity and saturation, and break through the performance bottleneck of traditional single doped pigments; (2) Superfine and uniform particle size: liquid phase method is used to mix at the molecular level, avoiding the coarse and uneven particles caused by solid phase grinding; citric acid as a complexing agent prevents component segregation during the precipitation process, realizing uniform mixing at the ion level from the precursor stage, ensuring the uniformity of the composition; F - in ammonium fluoride not only forms a stable structure with Zr 4+ in the liquid phase to form a uniform gel-like precipitate, but also acts as a mineralizer to promote low-temperature crystallization of zirconium silicate during calcination, and its high-temperature volatility inhibits abnormal grain growth and sintering, thereby achieving control of the particle size in a super-fine and uniform manner, and the obtained pigment particles have super-fine and uniform characteristics, and the D 50 particle size is controllable in the range of 200-500 nm with narrow distribution and no hard agglomeration, and has excellent dispersibility in glaze; (3) High temperature resistance: the matrix of the pigment of the present application is zirconium silicate (ZrSiO4) with extremely stable crystal structure, and the zirconium silicate lattice is very stable at high temperature (usually up to 1500°C or above), and is not easy to decompose, which provides a natural "protective shell" for the pigment, enabling it to withstand the high temperature environment during the firing process of ceramic glaze; at the same time, the color-developing Tb 4+ is stably solid-solved in the zirconium silicate lattice, and the Ce 4+ performs charge compensation, preventing Tb 4+ from being reduced to Tb 3 + during high-temperature heat treatment, ensuring that the main crystal phase and color-developing center of the pigment can still remain stable after high-temperature firing, thereby making the pigment have high temperature resistance; (4) Environmentally friendly and energy-saving process: traditional methods need to rely on strong corrosive chlorine gas atmosphere to maintain Tb 4+ , which not only pollutes the environment but also has safety hazards, while the present application, through the charge compensation effect of Ce 4+ , utilizes the redox properties of Ce ions to stabilize Tb 4+ in a conventional air atmosphere, and inhibits the reduction of Tb 4+ to Tb 3+ in an air atmosphere, and only one calcination in an air atmosphere is needed to stabilize Tb4+ Eliminate the use of harmful gases, no need for strong corrosive atmosphere assistance, solve the Tb 4+ The contradiction between stability and environmental protection production conforms to the green production concept; the traditional solid phase method has high calcination temperature (usually above 1200 DEG C), which easily leads to particle coarsening; although part of the liquid phase method reduces the temperature, the color performance is insufficient, the present application benefits from the high reactivity of the liquid phase method and the mineralization of ammonium fluoride, and the calcination temperature of the present application is also much lower than that of the traditional solid phase method, uniform grain growth can be realized in an air atmosphere, which avoids particle coarsening caused by high temperature and reduces energy consumption, and the process feasibility and energy saving demand are considered, the preparation method is simple and safe, and the energy consumption and cost are significantly reduced; (5) High product and process stability: liquid phase method ensures high mixing uniformity of components at atomic scale, ensures chemical uniformity from the source; stable zirconium silicate lattice structure and Tb 4+ Successfully solid-solved and stabilized therein, the main crystal phase of the product is pure zirconium silicate, the impurity phase is few, and the performance is stable, which gives the pigment excellent high temperature stability and chemical stability; through a series of control processes such as concentration, material adding sequence, aging, drying and calcination, the batch consistency of product quality is ensured, the process stability is high, and the batch reproducibility is high.

[0025] In summary, the present application can stably form tetravalent terbium in a mild air atmosphere through Tb / Ce co-doping and liquid phase synthesis process, effectively solve the color attenuation problem caused by superfine pigment, systematically solve the environmental protection hidden danger, performance contradiction and process complexity of traditional yellow zirconium-based pigment, and the prepared pigment has comprehensive advantages such as superfine particle size, high coloring power, high stability and high process feasibility, and has the characteristics of pure and saturated color, excellent dispersibility, environmental protection and energy saving, and good process stability, which provides a new technical path for the green and fine production of high-end ceramic yellow pigment. BRIEF DESCRIPTION OF DRAWINGS

[0026] Figure 1 SEM image of the Tb 0.06 Ce 0.06 Zr 0.88 SiO4 sample in Example 1.

[0027] Figure 2 XRD image of the Tb 0.06 Zr 0.94 SiO4 sample under different Ce contents.

[0028] Figure 3 UV image of the Tb 0.06 Zr 0.94 SiO4 sample under different Ce contents. DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved in the present application clearer, the present application will be further described in detail below in combination with the drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and not to limit the present application.

[0030] The present application first provides a preparation method of a high-temperature-resistant ultra-fine zirconium-based yellow ceramic colorant, comprising: The zirconium source, the terbium source and the cerium source are sequentially dissolved in deionized water to obtain a metal ion solution, wherein the concentration of zirconium ions in the metal ion solution is 0.1-3 mol / L, and the total concentration of terbium ions and cerium ions is 0.01-0.3 mol / L; Citric acid is added to the metal ion solution, and stirred uniformly to fully dissolve and complex, so as to obtain a complex solution; A mixed solution of tetraethyl orthosilicate and ethanol is added to the complex solution, and stirred uniformly to obtain a precursor mixed solution, wherein the concentration of silicon in the precursor mixed solution is 0.01-5 mol / L; Under vigorous stirring, an aqueous solution of the precipitant ammonium fluoride is slowly added dropwise to the precursor mixed solution, and after the addition is completed, the stirring is continued for a period of time to form a uniform white gel-like precipitate; The white gel-like precipitate is washed with water for multiple times and then washed with alcohol for multiple times, and then dried to obtain a precursor powder; The mineralizer is added to the precursor powder, and mixed sufficiently, and then calcined under an air atmosphere, and after the calcination is completed, the calcined product is cooled to room temperature in the furnace to obtain a calcined product; The calcined product is ground to obtain an ultra-fine zirconium-based yellow ceramic colorant.

[0031] In one embodiment, the zirconium source is zirconium oxychloride, the terbium source is terbium chloride, and the cerium source is cerium chloride. The present application only lists the most common substances, which can not be limited thereto.

[0032] Preferably, the concentration of zirconium ions in the metal ion solution is 0.5-2 mol / L.

[0033] Preferably, the total concentration of terbium ions and cerium ions in the metal ion solution is 0.01-0.2 mol / L.

[0034] In one embodiment, the ratio of the number of moles of citric acid to the total number of moles of metal ions of zirconium ions, terbium ions and cerium ions is (1.5-3.0):1.

[0035] In one embodiment, the concentration of silicon in the precursor mixed solution is 0.01-1 mol / L.

[0036] In one embodiment, the concentration of the precipitant ammonium fluoride aqueous solution is 1.0-4.0 mol / L, the precipitant ammonium fluoride aqueous solution is slowly added to the precursor mixed solution under vigorous stirring, after the addition is completed, the stirring is continued for 2-8 hours for aging, and a uniform white gel-like precipitate is formed.

[0037] In one embodiment, the white gel-like precipitate is washed with water for 2-6 times and then washed with ethanol for 2-6 times, and then dried at 80-120 ℃ for 12-24 h to obtain a precursor powder.

[0038] In one embodiment, 5-20 wt% of a mineralizer is added to the precursor powder, mixed well, and calcined under an air atmosphere, the calcination conditions being: heating at a rate of 2-5 ℃ / min to 800-1100 ℃, and maintaining the temperature for 20 min-4 h; after the calcination is completed, the furnace is cooled to room temperature to obtain a crude product. Specifically, the mineralizer is LiF.

[0039] Based on the above method, the application further provides a high-temperature-resistant superfine zirconium-based yellow ceramic colorant, the structure general formula of which is Tb x Ce y Zr 1-x-y SiO4; wherein 0

[0040] In order to further illustrate the technical solutions and technical effects of the application, some specific examples and comparative examples are provided below.

[0041] Example 1 (1) 32.2 g of ZrOCl2·8 H2O, 2.24 g of TbCl3·6 H2O and 1.48 g of CeCl3 were sequentially dissolved in 100 mL of deionized water, and stirred and ultrasonicated to fully dissolve the three, to obtain solution A.

[0042] (2) 43.03 g of C6H8O7 was added to solution A, and stirred and ultrasonicated to fully dissolve it.

[0043] (3) 25 g of TEOS was dissolved in 10 g of ethanol and homogenized for 5 min; under stirring, the dissolved TEOS was slowly added to the above complex solution, and stirred to obtain a precursor mixed solution.

[0044] (4) 7.4 g of NH4F was dissolved in 100 mL of deionized water, and stirred and ultrasonicated to fully dissolve it, to obtain a precipitant B.

[0045] (5) Slowly add the precipitant B to the precursor mixture obtained in step 3 under vigorous stirring. After the addition is completed, continue to stir and age for 4 h to form a uniform white gel-like precipitate.

[0046] (6) Wash the precipitate obtained in step 5 with water and ethanol respectively for 4 times. Then dry at 120 o C for 12 h to obtain the dried precursor powder.

[0047] (7) Add 5wt% LiF to the precursor powder and calcine under air atmosphere. The calcination conditions are: increase the temperature to 900

[0048] C at a rate of 5

[0049] Example 2 (1) Dissolve 32.2 g of ZrOCl2·8H2O, 2.24 g of TbCl3·6H2O and 1.48 g of CeCl3 in 100 mL of deionized water respectively, and stir and ultrasonicize to fully dissolve the three to obtain solution A.

[0050] (2) Add 43.03 g of C6H8O7 to solution A and stir and ultrasonicize to fully dissolve it.

[0051] (3) Dissolve 25 g of TEOS in 10 g of ethanol and homogenize for 5 min; slowly add the dissolved TEOS to the above complex solution under stirring, and stir uniformly to obtain a precursor mixture.

[0052] (4) Dissolve 7.4 g of NH4F in 100 mL of deionized water, and stir and ultrasonicize to fully dissolve it to obtain precipitant B.

[0053] (5) Slowly add the precipitant B to the precursor mixture obtained in step 3 under vigorous stirring. After the addition is completed, continue to stir and age for 4 h to form a uniform white gel-like precipitate.

[0054] (6) Wash the precipitate obtained in step 5 with water and ethanol respectively for 4 times. Then dry at 120 o C for 12 h to obtain the dried precursor powder.

[0055] (7) Add 5wt% LiF to the precursor powder and calcine under air atmosphere. The calcination conditions are: increase the temperature to 1050 o C at a rate of 5 oC, and keep the temperature for 2 h; after the calcination is completed, cool down to room temperature with the furnace.

[0056] (8) Grind the calcined product, and the final ultrafine zircon-based yellow ceramic colorant powder is obtained.

[0057] Example 3 (1) Dissolve 32.2 g of ZrOCl2·8H2O, 2.24 g of TbCl3·6H2O, and 1.95 g of CeCl3 in 100 mL of deionized water in sequence, and stir and ultrasonicize to fully dissolve the three, to obtain solution A.

[0058] (2) Add 43.03 g of C6H8O7 to solution A, and stir and ultrasonicize to fully dissolve it.

[0059] (3) Dissolve 25 g of TEOS in 10 g of ethanol, and homogenize for 5 min; under stirring, slowly drop the dissolved TEOS into the above complex solution, stir to be uniform, and obtain a precursor mixture.

[0060] (4) Dissolve 7.4 g of NH4F in 100 mL of deionized water, and stir and ultrasonicize to fully dissolve it, to obtain precipitant B.

[0061] (5) Slowly drop precipitant B into the precursor mixture obtained in step 3 under vigorous stirring. After the dropping is completed, continue to stir and age for 4 h, to form a uniform white gelatinous precipitate.

[0062] (6) Wash the precipitate obtained in step 5 with water and ethanol respectively for 4 times. Then dry at 120 o C for 12 h, to obtain dry precursor powder.

[0063] (7) Add 5wt% of LiF to the precursor powder, and perform calcination under air atmosphere. The calcination conditions are: increase the temperature to 900 o C at a rate of 5 o C / min, and keep the temperature for 2 h; after the calcination is completed, cool down to room temperature with the furnace.

[0064] (8) Grind the calcined product, and the final ultrafine zircon-based yellow ceramic colorant powder is obtained.

[0065] Example 4 (1) Dissolve 32.2 g of ZrOCl2·8H2O, 2.24 g of TbCl3·6H2O, and 1.48 g of CeCl3 in 100 mL of deionized water in sequence, and stir and ultrasonicize to fully dissolve the three, to obtain solution A.

[0066] (2) Add 21.52 g of C6H8O7 to solution A, and stir and ultrasonicize to fully dissolve.

[0067] (3) Dissolve 25 g of TEOS in 10 g of ethanol, and homogenize for 5 min; under stirring, slowly add the dissolved TEOS to the above complex solution, and stir to obtain a precursor mixture.

[0068] (4) Dissolve 7.4 g of NH4F in 100 mL of deionized water, and stir and ultrasonicize to fully dissolve to obtain a precipitant B.

[0069] (5) Slowly add the precipitant B to the precursor mixture obtained in step 3 under vigorous stirring. After the addition is completed, continue to stir and age for 4 h to form a uniform white gel-like precipitate.

[0070] (6) Wash the precipitate obtained in step 5 with water and ethanol respectively for 4 times. Then dry at 120 o C for 12 h to obtain a dry precursor powder.

[0071] (7) Add 5wt% of LiF to the precursor powder, and calcine under an air atmosphere. The calcining conditions are as follows: increase the temperature to 900 o C at a rate of 5 o C / min, and keep the temperature for 2 h; after the calcination is completed, cool to room temperature in the furnace.

[0072] (8) Grind the calcined product to obtain a final ultrafine zircon-based yellow ceramic pigment powder.

[0073] Example 5 (1) Dissolve 32.2 g of ZrOCl2·8 H2O, 2.24 g of TbCl3·6 H2O and 1.48 g of CeCl3 in 100 mL of deionized water respectively, and stir and ultrasonicize to fully dissolve the three to obtain a solution A.

[0074] (2) Add 43.03 g of C6H8O7 to solution A, and stir and ultrasonicize to fully dissolve.

[0075] (3) Dissolve 25 g of TEOS in 10 g of ethanol, and homogenize for 5 min; under stirring, slowly add the dissolved TEOS to the above complex solution, and stir to obtain a precursor mixture.

[0076] (4) Dissolve 3.7 g of NH4F in 100 mL of deionized water, and stir and ultrasonicize to fully dissolve to obtain a precipitant B.

[0077] (5) Slowly add precipitant B into the precursor solution obtained in step 3 under vigorous stirring. After the addition is completed, continue to stir and age for 4 h to form a uniform white gel-like precipitate.

[0078] (6) Wash the precipitate obtained in step 5 with water and ethanol for 4 times, respectively. Then dry at 120 o C for 12 h to obtain dry precursor powder.

[0079] (7) Add 5wt% LiF into the precursor powder and calcine under air atmosphere. The calcination conditions are as follows: increase the temperature to 900 o C at a rate of 5 o C / min, and keep the temperature for 2 h; after the calcination is completed, cool down to room temperature in the furnace.

[0080] (8) Grind the calcined product to obtain the final ultra-fine zircon-based yellow ceramic pigment powder.

[0081] Comparative Example 1 Conventional ultra-fine Tb x Zr 1-x SiO4 yellow pigment: (1) Dissolve 32.2 g ZrOCl2·8H2O and 2.24 g TbCl3·6H2O in 100 mL deionized water to obtain solution A; (2) Dissolve 34.08 g Na2SiO3·9H2O in 100 mL deionized water to obtain solution B; (3) Co-drip the above prepared solutions A and B into 100 mL deionized water to obtain a precursor solution; (4) Place the precursor solution in a water bath and age at room temperature for 4 h, wash with water and ethanol for 3-4 times, respectively, and then dry at 120°C in an oven for 24 h to obtain precursor powder.

[0082] (5) Add 5wt% LiF into the precursor powder and mix well.

[0083] (6) Load the obtained mixed powder into a ceramic crucible, and heat to 1100°C at a rate of 5°C / min under air atmosphere for 2 h treatment.

[0084] (10) Grind the calcined product through a 400 mesh sieve to obtain conventional zircon-based yellow ceramic pigment powder.

[0085] (11) 50 g of the colorant powder described above is loaded into a ball mill tank, and ball milling is performed, the ball milling medium is selected from zirconium beads with a diameter of 0.3-0.4, the grinding solvent is ethylene glycol, and the grinding aid is triethanolamine (the addition amount is 0.5 wt% of the mass of the colorant), and the ball milling parameters are set as follows: rotation speed 2000 r / min, time 60 min, and finally, the ultrafine powder is obtained.

[0086] For the above examples and comparative examples, as shown in Table 1, it can be known that in the examples of the present application, the best product is ZrSiO4, D 50 The values of D50 of the ultrafine zirconium-based yellow colorants prepared by the examples are all less than 1 micron, and the yellowness values of the ultrafine zirconium-based yellow colorants prepared by the examples are higher. Among them, the values of D50 of the ultrafine zirconium-based yellow colorants prepared by Example 2 and Example 5 are relatively small compared with other examples, and the yellowness value of the ultrafine zirconium-based yellow colorant prepared by Example 2 is higher than that of Example 5. In summary, Example 2 can be regarded as the best example, and in actual application, the preparation method of Example 2 can be used to prepare the ultrafine zirconium-based yellow colorant.

[0087] Table 1 Comparison of results of examples and comparative examples Figure 1 The SEM image of the Tb 0.06 Ce 0.06 Zr 0.88 SiO4 sample in Example 1 shows that the particle size of the ultrafine zirconium-based yellow ceramic colorant prepared by the present application is in the submicron range.

[0088] Figure 2 The XRD image of the Tb 0.06 Zr 0.94 SiO4 sample under different Ce contents shows that with the increase of the addition amount of Ce, the phase composition of the system is zirconium silicate.

[0089] Figure 3 The UV image of the Tb 0.06 Zr 0.94 SiO4 sample under different Ce contents shows that with the increase of the addition amount of Ce, the reflectivity in the high reflection region (470-650 nm) increases, accompanied by red shift, and the yellowness value (b*) increases.

[0090] The preferred embodiments of the present application are described in detail above in combination with the drawings and specific examples, but the present application is not limited to the specific details in the above-described embodiments, and various simple modifications can be made to the technical solutions of the present application within the technical concept of the present application, and these simple modifications all belong to the protection scope of the present application.

Claims

1. A method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment, characterized in that, include: Zirconium source, terbium source and cerium source are dissolved sequentially in deionized water to obtain a metal ion solution. In the metal ion solution, the concentration of zirconium ions is 0.1–3 mol / L and the total concentration of terbium ions and cerium ions is 0.01–0.3 mol / L. Add citric acid to the metal ion solution, stir until fully dissolved and complexed to obtain a complexed solution; A mixture of tetraethyl orthosilicate and ethanol is added to the complexation solution and stirred until homogeneous to obtain a precursor mixture, wherein the concentration of silicon in the precursor mixture is 0.01–5 mol / L. Under vigorous stirring, the ammonium fluoride aqueous solution of the precipitant was slowly added dropwise to the precursor mixture. After the addition was completed, stirring and aging continued for a period of time to form a uniform white gel-like precipitate. The white gel-like precipitate was washed with water several times, then washed with alcohol several times, and then dried to obtain the precursor powder. Add mineralizer to precursor powder, mix thoroughly, calcine in air atmosphere, and cool to room temperature with furnace after calcine to obtain calcined product; The calcined product was ground to obtain an ultrafine zirconium-based yellow ceramic pigment.

2. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 1, characterized in that: The zirconium source includes zirconium oxychloride; the terbium source includes terbium chloride; and the cerium source includes cerium chloride.

3. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 2, characterized in that: The zirconium ion concentration in the metal ion solution is 0.5–2 mol / L.

4. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 3, characterized in that: The total concentration of terbium and cerium ions in the metal ion solution is 0.01–0.2 mol / L.

5. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 4, characterized in that: The ratio of the number of moles of citric acid to the total number of moles of zirconium, terbium, and cerium ions is (1.5–3.0):

1.

6. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 1, characterized in that: The silicon concentration in the precursor mixture is 0.01–1 mol / L.

7. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 6, characterized in that: The concentration of the ammonium fluoride aqueous solution as a precipitant is 1.0–4.0 mol / L. Under vigorous stirring, the ammonium fluoride aqueous solution as a precipitant is slowly added dropwise to the precursor mixture. After the addition is complete, stirring and aging continue for 2–8 hours to form a uniform white gel-like precipitate.

8. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 7, characterized in that: The white gel-like precipitate was washed with water 2-6 times, then washed with ethanol 2-6 times, and then dried at 80-120 °C for 12-24 h to obtain the precursor powder.

9. The method for preparing a high-temperature resistant ultrafine zirconium-based yellow ceramic pigment according to claim 8, characterized in that: Add 5–20 wt% mineralizer to the precursor powder, mix thoroughly, and calcine in an air atmosphere. The calcination conditions are: heat to 800–1100 ℃ at a rate of 2–5 ℃ / min, and hold at this temperature for 20 min–4 h. After calcination, cool to room temperature with the furnace to obtain the crude product.

10. A high-temperature resistant ultrafine zirconium-based yellow ceramic pigment based on the method of any one of claims 1-9, characterized in that: The zirconium-based yellow ceramic pigment has the general structural formula Tb x Ce y Zr 1-x-y SiO4; where 0 < x < 1, 0 < y < 1, and 0 < 1 - xy < 1.